Hearing Status and Etiology of Hearing Impairment Among the Patients Visiting Audiology OPD - Yadav, Ashok Kumar; Yadav, Pramodman Singh (Nepalese Medical Journal, 2024)
Introduction: Hearing disability can impair individual quality of life. It can impede communication, disrupt an individual's psychological and social well-being, and cause them to become socially isolated. We aimed to study the hearing status and etiology of hearing impairment in the patients visiting ENT-Audiology OPD. Materials and Methods: This cross-sectional study was conducted in the ENT-Audiology Department at the National Medical College and Teaching Hospital. Patients suspected of hearing impairment were audiologically evaluated with a MAICO 52 audiometer. A pure tone audiogram was done in each ear of every individual separately and a copy of it was kept along with demographic data and clinical history. Results: Among 410 individuals, 51.9% were males and 48.1% were females; a maximum of individuals were 16-30 (36.6%) years and the mean age was 33.56. Among 410 (820 ears) individuals 16.34%had unilateral hearing impairment and 67.31 %had bilateral hearing impairment. In 686 pathological ears, 51.45% suffered from otitis media followed by presbycusis in 14.47%. The conductive type of hearing impairment in 36.21% of patients and a mild degree of hearing impairment in 36.34% of patients were the most common. Conclusions: The prevalence of hearing impairment in this region is high. Otitis media was found to be the main cause of hearing disability and a mild degree of hearing loss was more evident. Preventive measures, early identification, and treatment can reduce hearing-disabling conditions.